I did a little evaluation of the function $-\ln(1-x)$ with a sum of an infinite series, but I have come to a contradiction, and I would like to ask your help to find my mistake.

Let us start with the sum: $$\sum_{i=0}^\infty x^k = \frac{1}{1-x}$$ which converges at $|x|<1$. Then, divide it by $x$ and we will get: $$\sum_{i=0}^\infty x^{k-1} = \frac{1}{x(1-x)}$$ Now, we will integrate the infinite sum (which we can for all $|x|<1$), and we will receive: $$\sum_{i=0}^\infty \frac{x^k}{k} = \int_0^x\frac{1}{t(1-t)}$$

Now, the contradiction comes by the fact that the infinite sum at the left part equals $-\ln(1-x)$, while by using integration by parts for the integral in the right we get: $$\ln(t)+\ln(1-t)|_0^x$$ which diverges because of $\ln(0)$, and isn't equal to $-\ln(1-x)$.

As I stated above, I obviously have a mistake somewhere, and would be happy to get your help, thanks!

  • 3
    $\begingroup$ You have a sum over $i$ of $x^k$. Whatever, the sum starts at zero, so the $x^k/k$ term is wrong. $\endgroup$ – Gerry Myerson May 19 '17 at 10:38
  • 1
    $\begingroup$ Gerry - you're right, I've missed that. thanks! $\endgroup$ – Mickey May 19 '17 at 10:49

Since, for $|x| < 1$ we have $$\frac{1}{1-x} = \sum_{k = 0}^\infty x^k.$$ Now since $$\int \frac{1}{1-x} dx = -\ln(1-x).$$ So that $$-\ln(1-x) = \int \left(\sum_{k = 0}^\infty x^k\right) dx = \sum_{k = 0}^\infty \frac{x^{k+1}}{k+1} ~\mbox{for} ~|x| < 1$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.